Optimal control in a model for Zika transmission with stratification by sex (Selecciones Matemáticas, 2020)
This paper presents an optimal control strategy for the Zika virus disease with sexual transmission. A mathematical model for the transmission of the Zika virus is considered with three preventive measures as control, namely: the prevention of the sexual contagion with the use of condoms and the orientation in the transmission of Zika in the homosexual and heterosexual relations, the campaigns against vectors and the protection of the society regarding the contagion by mosquito bites. We examine the implementation of various combinations of the control strategies in order to determine the most cost-effective one. The necessary conditions for the optimal controls are determined using Pontryaguin’s maximum principle and the optimality problem is solved using Runge-Kutta fourth order scheme. Based on the computational results, we conclude that the most efficient control strategy is when it is applied on the infections in homosexual relationships combined with the control in the transmission by vectors.